The Jahn-Teller effect: fundamentals and implications for physics and chemistry - Köppel, Horst; Barentzen, Heinz; Yarkony, David (Springer-Verlag Berlin Heidelberg, 2009)
The Jahn-Teller effect continues to be a paradigm for structural instabilities and molecular dynamical processes. This volume provides a survey of the current Jahn-Teller interactions at the interface of quantum chemistry and condensed matter physics.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Konferenzschrift; Jahn-Teller-Effekt